2011
DOI: 10.1371/journal.pone.0025671
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Evolution of HIV/AIDS in China from 1989–2009 to Inform Future Prevention and Control Efforts

Abstract: BackgroundTo determine policy implications, this analysis tracks the evolution of HIV/AIDS infection across China to understand current trends and potential risk factors.Methods and Principal FindingsA retrospective study with spatial analytical model and multilevel spatial models was conducted among 326,157 HIV/AIDS cases reported from 1989–2009. The results indicate that the distribution of HIV/AIDS was clustered at the county level with different directional distributions across China from 2003 to 2009. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…This may partially explain why the people who are 50 years older and students have occupied an increasing proportion of the total reported HIV cases in China [2]. Additionally, it also explains the male-to-female ration among reported national over 65 years people PLWHs increased rapidly in recent years [30]. Similar evidence was also reported among MSM students by recent study, which found that unprotected homosexual behavior accounted more and more HIV infection among reported HIV infection cases in China, male-to-male homosexual route infection accounted for 17.5% of the total reported student HIV infection cases in 2006, but this figure rapidly increased to 62.4% in 2009 [31].…”
Section: Discussionmentioning
confidence: 99%
“…This may partially explain why the people who are 50 years older and students have occupied an increasing proportion of the total reported HIV cases in China [2]. Additionally, it also explains the male-to-female ration among reported national over 65 years people PLWHs increased rapidly in recent years [30]. Similar evidence was also reported among MSM students by recent study, which found that unprotected homosexual behavior accounted more and more HIV infection among reported HIV infection cases in China, male-to-male homosexual route infection accounted for 17.5% of the total reported student HIV infection cases in 2006, but this figure rapidly increased to 62.4% in 2009 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, sexual transmission has become the dominant route of HIV transmission in China 1. The percentage of cases attributed to homosexual transmission rose from 7.3% in 2005 to 16.1% in 2011, comprising an increasing proportion of such infections among people living with HIV/AIDS (PLWHA) 2.…”
Section: Introductionmentioning
confidence: 99%
“…40 The association between sexually transmitted diseases and human migration along national highways has also been shown. [41][42][43][44][45] Persistence of EIEC infections in Borbón may be attributed to its higher population density compared with surrounding communities.…”
Section: Discussionmentioning
confidence: 99%